Adverse Drug Reactions in Bangladeshi Health Care Setup: An Update - Mainul, Haque; Badar Uddin, Umar (Research Journal of Pharmacy and Technology, 2015)
The safety of medicines has been a major issue involving health care delivery systems worldwide. Adverse drug reactions (ADRs) cause a huge burden accounting for considerable morbidity, mortality, and extra costs both developed and developing nations. Monitoring ADRs and pharmacovigilance (PV) is not adequate in many developing countries like Bangladesh. A literature search revealed only a few publications on ADRs in Bangladesh. These scientific reports revealed that the rate of ADRs are comparable with many countries, but the alarming issue is regulatory agencies are not much concern about the atrocities of ADRs. Despite the existing functional government organizations for monitoring ADRs which reports ADR cases to the WHO, it fails to keep pace with the current global situation. The Government of Bangladesh and other stakeholders should take up immediate initiatives in boosting up monitoring, and enhance awareness to report ADRs by the doctors, nurses, pharmacist and patients. PV studies and research on ADRs in Bangladesh should be encouraged.